2022
DOI: 10.1177/0961463x211070679
|View full text |Cite
|
Sign up to set email alerts
|

Ruminating on the past may be bad for you, or is it? Implications of past negative time perspective on job-related stress

Abstract: Past negative time perspective (PNTP), characterized by rumination on painful past experiences, is generally considered harmful to a person’s well-being. However, there is reason to suspect that a PNTP may not make matters worse if a high PNTP is consistent with culture, as in the case of India. Drawing on the person–culture matching hypothesis, we test the moderating effects of PNTP on the relationship between role stressors and both psychological strain and organizational outcomes among Indian employees in I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…Given the central importance of culture to both time perspectives and conflict style differences, scales which more explicitly consider cultural influences might be particularly useful (e.g., Oetzel et al, 2000). Recent scholarship indicates that even taken-for-granted associations of time perspectives with specific outcome variables may be culturally based; for example, Glazer et al (2022) found that having a high past negative time orientation is not positively associated with adverse responses to stressors in India, as might be more common in Western cultures.…”
Section: Future Researchmentioning
confidence: 99%
“…Given the central importance of culture to both time perspectives and conflict style differences, scales which more explicitly consider cultural influences might be particularly useful (e.g., Oetzel et al, 2000). Recent scholarship indicates that even taken-for-granted associations of time perspectives with specific outcome variables may be culturally based; for example, Glazer et al (2022) found that having a high past negative time orientation is not positively associated with adverse responses to stressors in India, as might be more common in Western cultures.…”
Section: Future Researchmentioning
confidence: 99%